2004
DOI: 10.1073/pnas.0400227101
|View full text |Cite
|
Sign up to set email alerts
|

Repriming the actomyosin crossbridge cycle

Abstract: The central features of the mechanical cycle that drives the contraction of muscle are two translational steps: the working stroke, whereby an attached myosin crossbridge moves relative to the actin filament, and the repriming step, in which the crossbridge returns to its original orientation. Although the mechanism of the first of these is understood in some detail, that of the second has received less attention. Here, we show that repriming occurs after detachment of the crossbridge from the actin, rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…2 However, these myosin-ligand complexes promote an open switch II conformation of myosin (compared with the closed switch II conformation of M-ADP-P i ) (7)(8)(9) and may also change the mechanism of myosin binding to actin. Supporting this view are single molecule mechanical measurements which show that fast skeletal myosin complexed with ligands that produce an open switch II conformation do not produce a power stroke upon binding to actin (10). It is, therefore, likely that the regulation of the binding of myosin to thin filaments in the open conformation may not give an accurate description of the mechanism of the regulation of thin filament accelerated product dissociation from M-ADP-P i .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…2 However, these myosin-ligand complexes promote an open switch II conformation of myosin (compared with the closed switch II conformation of M-ADP-P i ) (7)(8)(9) and may also change the mechanism of myosin binding to actin. Supporting this view are single molecule mechanical measurements which show that fast skeletal myosin complexed with ligands that produce an open switch II conformation do not produce a power stroke upon binding to actin (10). It is, therefore, likely that the regulation of the binding of myosin to thin filaments in the open conformation may not give an accurate description of the mechanism of the regulation of thin filament accelerated product dissociation from M-ADP-P i .…”
mentioning
confidence: 87%
“…It is now generally accepted that myosin exists in two or more conformations and that the conformation is dependent upon the ligands bound to the active site. Of the ligands listed above, only ADP-P i predominately produces the "closed" switch II conformation of the myosin nucleotide binding site that is required to produce a power stroke when the myosin binds to actin (10).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical Analysis-To determine the pCa value at halfmaximal fluorescence change (pCa 50 ) in reconstituted thin filament or force generation in skinned fiber and the Hill coefficient (n H ), the fluorescence and force were normalized to maximum. The relationship of fluorescence change or force generation with pCa was fit to a modified Hill equation (25,30).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of actin activated hydrolysis of GTP is some 40 times less than for ATP (10 C, low ionic strength; White et al 1993). We observed that in the optical trap the interaction rate, far from being much lower, was in fact significantly higher with GTP, ITP and ATPcS than with ATP (Steffen & Sleep 2004; see table 2). For dumbbell experiments, the duration of events is strictly controlled by the second-order rate of NTP binding but the rate of observing events is critically dependent on the exact position of the dumbbell with respect to the fixed myosin bearing bead, thus a relatively large number of experiments are needed to make a comparison.…”
Section: The Repriming Stepmentioning
confidence: 76%
“…The displacements of the dumbbell observed in the presence of NTP are shown in table 2 (Steffen & Sleep 2004). In each case, the value is not significantly different from zero and thus we conclude that M Á GTP, M Á ITP and M Á ATPcS all bind to actin in the same conformational state as the final AM rigor state.…”
Section: The Repriming Stepmentioning
confidence: 99%